PENYUSUTAN ARSIP DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA MADIUN - Faizah, Fidrotul Aulia; Lisdiantini, Netty; Syarifah, Ina (Politeknik Negeri Madiun, 2024)
Archives are records of activities presented in various forms of media and used as information materials that have utility value for an organization or agency and are stored in such a way that if needed at any time they can be easily and quickly found again. Given the importance of records, every organization or agency needs to have a Records Division to manage them. One of the activities carried out in records management is disposition. Records disposition is the activity of separating active records from inactive records and removing useless records based on the records retention schedule. This study was conducted to find out the stages of implementing records disposition in Dinas Perpustakaan dan Kearsipan Kota Madiun. The method used is descriptive qualitative. Based on the study results, it was concluded that records disposition has included three stages, namely transfer, destruction, and submission.